MINERAL SEBAGAI TERAPI KOMPLEMENTER UNTUK DISMENORE PRIMER - Rista Dwi Hermilasari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Primary dysmenorrhea is menstrual pain that is generally experienced by women of reproductive age due to increased prostaglandin synthesis. This condition can reduce academic performance and daily activities. The use of NSAIDs causes side effects, so a nutritional intervention approach is needed, one of which is mineral consumption. The aim of this study was to examine the effects of minerals as complementary and alternative treatments for primary dysmenorrhea. Literature search through PubMed, ScienceDirect, and Google Scholar databases with primary keywords dysmenorrhea, magnesium, calcium, zinc, pain reduction, menstrual pain and obtained 6 articles that met the criteria. Several types of minerals such as calcium, magnesium, boron, and zinc are effective in reducing pain intensity through prostaglandin inhibition, regulation of uterine muscle contractility, and antioxidative and anti-inflammatory effects. Mineral consumption has the potential to be a non-pharmacological complementary therapy for treating primary dysmenorrhea. Further clinical studies are needed to strengthen clinical recommendations.